Digital-Based Economic Recovery Program For MSMEs in Indonesia - Febrianur Ibnu Fitroh Sukono Putra; Herry Subagyo; Risanda A. Budiantoro; Awanis L. Haziroh (LPPM Universitas Terbuka, 2022)
Purpose - The recent Covid-19 pandemic has stagnated the majority of economic sectors, especially Micro-enterprises. This is observed in the inability of most Micro-enterprises to develop during the period, thereby, leading to bankruptcy and a change in sales strategy through a digitalization scheme to obtain more comprehensive marketing access. Therefore, this research was conducted to initiate the ideal e-marketing adoption model for small micro-enterprises. Methodology - This research uses qualitative exploration approach. The samples were selected using snowball sampling technique by moving gradually from one individual to another. Moreover, the analyzed through data collection, reduction, presentation, and conclusion. Findings - The results showed that there are two categories of digital business programs which include startup training and development as well as scale-up training and development. The main contribution of the implementation of the Digital-Based Economic Recovery Program is facilitating the micro-enterprises in Indonesia accessibility to become participants in sustainable empowerment, increasing the micro-enterprises in Indonesia business performance capacity, and encouraging the micro-enterprises competitiveness increased to penetrate the suitable international market standards. Originality - The program is expected to serve as a role model based on mutual relations to ensure optimal empowerment of Micro-enterprises supported by the use of appropriate technology.